Adiciones y revisiones al Atlas de la flora vascular silvestre de Burgos, VI [Additions and revisions to “Atlas de la Flora Silvestre de Burgos”, VI] - Juan A. ALEJANDRE SÁENZ; Pablo BARBADILLO ESCRIVÁ DE ROMANÍ; Juan José BARREDO PÉREZ; Javier BENITO AYUSO; María Josefa ESCALANTE RUIZ; Javier María GARCÍA-LÓPEZ; Raquel María GARCÍA VALCARCE; Luis MARÍN PADELLANO; Gonzalo MATEO SANZ; Carlos MOLINA MARTÍN; Gonzalo MONTAMARTA PRIETO; Miguel Ángel PINTO CEBRIÁN; et al. (Flora Montiberica, 2012)
RESUMEN: Se mencionan 59 táxones con citas o comentarios referidos a su existencia en la provincia de Burgos. De ellos, 11 suponen una novedad para el catálogo provincial. SUMMARY: 59 taxa with either quotations or remarks, related to their existence within the province of Burgos, are mentioned. 11 out of these aforementioned ones mean a novelty value for the provincial catalogue.